Exploring public wearable display of wellness tracker data. Issue 138 (June 2020) - Colley, Ashley; Pfleging, Bastian; Alt, Florian; Häkkilä, Jonna
Highlights: Two functional wearable tracker display prototypes, the hat tracker and the tracker badge are presented. Insights on perceived experiences of the prototypes from focus group and in the wild studies are reported. The motivating nature of such displays was appreciated, but users favor the display of positive information. Leveraging prior work, a model describing the factors affecting users' willingness to share tracked data via wearable displays is presented. Abstract: We investigate wearable presentation of tracked wellness data, and people's perceptions and motivations for sharing it through a wearable display. Whilst online sharing is a common feature in wellness tracking solutions, the motivations and experiences of users to share tracked data in situ has not been widely studied. We created two functional prototypes – the hat tracker and the tracker badge – which we used as probes in two focus groups to elicit opinions on the content and format of wearable tracker displays. Complementing this, a study where participants used the hat tracker prototype in public locations provides insights on sharing in everyday life use contexts. We report that users appreciate the motivating nature of such displays, but favor the display of positive information. Leveraging prior work, we present a model describing the factors affecting users' willingness to share tracked data via wearable displays, and highlight such displays' potential for supporting behavior change.